Acute lobar nephritis in children: Not so easy to recognize and manage. - Bibalo, Cristina; Apicella, Andrea; Guastalla, Veronica; Marzuillo, Pierluigi; Zennaro, Floriana; Tringali, Carmela; Taddio, Andrea; Germani, Claudio; Barbi, Egidio (World J Clin Pediatr, 2016)
Acute lobar nephritis (ALN) is a localized non-liquefactive inflammatory renal bacterial infection, which typically involves one or more lobes. ALN is considered to be a midpoint in the spectrum of upper urinary tract infection, a spectrum ranging from uncomplicated pyelonephritis to intrarenal abscess. This condition may be difficult to recognize due to the lack of specific symptoms and laboratory findings. Therefore the disease is probably underdiagnosed. Computed tomography scanning represents the diagnostic gold standard for ALN, but magnetic resonance imagine could be considered in order to limit irradiation. The diagnosis is relevant since initial intravenous antibiotic therapy and overall length of treatment should not be shorter than 3 wk. We review the literature and analyze the ALN clinical presentation starting from four cases with the aim to give to the clinicians the elements to suspect and recognize the ALN in children.

Decline in Lung Function in Childhood Asthma. - Bibalo, Cristina; Longo, Giorgio; Ventura, Alessandro (N Engl J Med, 2016)
Keywords: Anti-Inflammatory Agents; Asthma; Female; Humans; Lung; Male

Relapse and metastasis of atypical teratoid/rhabdoid tumor in a boy with neurofibromatosis type 1 treated with recombinant human growth hormone. - Tornese, Gianluca; Faleschini, Elena; Matarazzo, Lorenza; Bibalo, Cristina; Zanazzo, Giulio Andrea; Rabusin, Marco; Tonini, Giorgio; Zennaro, Floriana; Ventura, Alessandro (Neuropediatrics, 2015)
Even though no increased recurrence rate seems to be reported in patients with brain tumors receiving recombinant human growth hormone (rhGH) replacement, in some patients multiple risk factors could put at higher risk for recurrence. In such cases, the decision to start rhGH therapy should be very cautious. A boy with neurofibromatosis type 1 developed an atypical teratoid/rhabdoid tumor (AT/RT) of right cerebellum, treated with surgery, radiotherapy, and chemotherapy. After 3 years of remission, he started rhGH for growth hormone deficiency, having a negative magnetic resonance imaging (MRI) scan. Ten weeks after starting therapy, the boy became symptomatic and MRI showed relapse of AT/RT in the right cerebellum and a new lesion in the brainstem. The boy died of progressive disease. In this case, the connection between AT/RT recurrence and the beginning of rhGH therapy, with a negative pretreatment MRI, cannot be excluded. Additional caution should be used for rhGH in patients with multiple risk factors.
Keywords: Brain Stem Neoplasms; Cerebellar Neoplasms; Child; Human Growth Hormone; Humans; Magnetic Resonance Imaging; Male; Neurofibromatosis 1; Recombinant Proteins; Recurrence; Rhabdoid Tumor; Risk Factors; Teratoma

Treatment of asthma based on symptoms. - Bibalo, Cristina; Longo, Giorgio; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Asthma; Female; Humans; Male; Spirometry